Efek Gaya Asuh Permisif Terhadap Kendala Pembentukan Kepribadian Siswa Sekolah Dasar - Rekno Handayani; Imaniar Purbasari; Deka Setiawan (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2020)
This research is to find out more deeply about the effect of permissive parenting style on the constraints of the personality formation of class IV elementary school students 1 Gulang MejoboKudus. Descriptive qualitative is the method used to carry out research. Using direct observation, interviews, notes, and documentation as research instruments.Analysis of the data used is the Milles-Huberman model presented interactively until the data becomes saturated.The results showed that the results showed that permissive parenting style had an unfavorable effect on the personality formation of fourth grade students of SD 1 Gulang. This is due to the lack of parental control over children so that children experience irregularities in their learning. As for attitudes and characteristics that show less well in students,especially in learning,namely (1) lack of interest in learning, (2) passivity in learning, (3) low student confidence, (4) low learning outcomes. so it can be concluded that the less than maximum assistance will provide obstacles in the formation of the personality of class IV elementary school students 1 Gulang. Input in this study is for parents to be able to accompany their children and not give too much leeway to a child. Keywords: Permissive parenting, Personality, Elementary school students